Feasibility assessment of climate change adaptation options across Africa: an evidence-based review. (25th June 2021) - Williams, Portia Adade; Simpson, Nicholas Philip; Totin, Edmond; North, Michelle A; Trisos, Christopher H
Abstract: Considering the feasibility and effectiveness of adaptation options is essential for guiding responses to climate change that reduce risk. Here, we assessed the feasibility of adaptation options for the African context. Using the Global Adaptation Mapping Initiative, a stocktake of adaptation-related responses to climate change from the peer-reviewed literature in 2013–2020, we found 827 records of adaptation actions in Africa. We categorised and evaluated 24 adaptation options and for each option, six dimensions of feasibility were considered: economic, environmental, social, institutional, technological, and evidence of effectiveness. Over half (51%) of all adaptation actions were reported in the food sector where sustainable water management (SWM) was the most reported option. The fewest actions were reported for cities (5%). The majority of actions (53%) were recorded in just six countries: Ghana, Ethiopia, Kenya, Tanzania, Nigeria and South Africa. Encouragingly, effectiveness was assessed as medium or high for 95% of adaptation options. However, no options had high feasibility on any other dimension. Technological and institutional factors present major barriers to implementation. Crop management, SWM, sustainable agricultural practices, agroforestry, livelihood diversification, ecosystem governance and planning, health governance and planning, infrastructure and built environment, all had moderate feasibility across three or more dimensions. Human migration has low feasibility but high potential for risk reduction. Major knowledge gaps exist for environmental feasibility, for assessing adaptation limits at increasing levels of climate hazard, for economic trade-offs and synergies, and for Central and Northern Africa. Our results highlight sectors where enablers for adaptation can be increased. Future assessments can apply the method established here to extend findings to other national and local levels.